2018
DOI: 10.1021/acs.orglett.8b02228
|View full text |Cite
|
Sign up to set email alerts
|

LiHMDS-Promoted Palladium or Iron-Catalyzed ipso-Defluoroborylation of Aryl Fluorides

Abstract: A novel and efficient method for the synthesis of arylboronic acid pinacol esters via a palladium- or iron-catalyzed cross-coupling reaction of aryl fluorides with bis(pinacolato)diboron (Bpin) in the presence of LiHMDS was developed. The Pd-catalyzed defluoroborylation of fluoroarenes is compatible with a variety of functional groups such as primary and secondary amine, ketone, trifluoromethyl, alkoxy, and boryl. Remarkably, no external ligand is required for enhanced conversion efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 57 publications
(30 reference statements)
2
22
0
1
Order By: Relevance
“…Cao et al reported an iron-catalyzed defluoroborylation of aryl fluorides promoted by LiHMDS in the mixture solvents (Scheme 14). [54] This method could synthesize aryl boronate esters through the cross-coupling reaction of aryl fluorides with B 2 pin 2 without the use of ligands. However, only biaryl fluorides were suitable for this system, and the desired products were obtained in moderate yields.…”
Section: Iron-catalyzed Csp 2 à B Bond Formationmentioning
confidence: 99%
“…Cao et al reported an iron-catalyzed defluoroborylation of aryl fluorides promoted by LiHMDS in the mixture solvents (Scheme 14). [54] This method could synthesize aryl boronate esters through the cross-coupling reaction of aryl fluorides with B 2 pin 2 without the use of ligands. However, only biaryl fluorides were suitable for this system, and the desired products were obtained in moderate yields.…”
Section: Iron-catalyzed Csp 2 à B Bond Formationmentioning
confidence: 99%
“…The reaction mechanism of the coupling reactions with 1-fluoro-2,2-diiodovinylarenes is not clear at this time. 14 We found that C−F bond of fluoroalkenes 6b and 7b can be activated by palladium to react with bis(pinacolato)diboron (B 2 Pin 2 ) to furnish the corresponding vinylboranes with good yields (Scheme 6). 15 In summary, we have developed a simple and efficient method for the synthesis of 1-fluoro-2,2-diiodovinylarenes via the decarboxylation of alkynoic acids.…”
Section: Scheme 3 Control Experimentsmentioning
confidence: 99%
“…从 XPS 的元素分析 结果可以看出(表 S1), 相比于 H-CMP, F-CMP 在含有碳 和氧的同时, 氟元素的含量也达到 11.74 wt%, 证实了 聚合物中氟元素的成功引入. F-CMP 中氟含量比理论值 低, 可能是因为在过渡金属钯的催化下, 聚合过程中部 分缺陷处的碳氟键断裂, 氟元素以氟负离子的形式离 去 [34] . [35] .…”
Section: 结果与讨论unclassified